AVALIAÇÃO DA ESTRATÉGIA DE AGRUPAMENTO DE AMOSTRAS DE ESCARRO EM UM PROGRAMA DE TRIAGEM EM MASSA PARA TUBERCULOSE EM PESSOAS PRIVADAS DE LIBERDADE - Dâmaris Batestin Porto silva (2024)
1.Introduction: Tuberculosis (TB) is the second leading cause of death, caused by a single etiological agent, second only to COVID-19. In countries with high endemicity, such as Brazil, there are some vulnerable populations susceptible to TB, such as people deprived of liberty (PPL). Brazil is ranked, worldwide, as the 3rd country with the highest number of PPL, being considered a target audience for TB control actions, such as mass testing. 2.Objective: To evaluate the strategy for pooling sputum samples in a mass screening program for TB in the PPL of Mato Grosso do Sul, Brazil. 3.Methodology: Cross-sectional descriptive study, mass screening for active TB was carried out in four prisons in Campo Grande in Mato Grosso do Sul, Brazil, between November 2021 and May 2022. All prisons were closed regime, which included men over 18 years old, and were coded as A, B, C and D. Sociodemographic and clinical data were collected through a standardized interview questionnaire. All participants subsequently consented and provided a sputum sample regardless of TB symptoms. The samples were tested by pooling 8 sputum samples in the GeneXpert MTB/RIF Ultra, followed by individual testing with culture in Ogawa-Kudoh medium, of those that were positive in the pooled test. 4.Results: We tracked >95% of PPL (n=4564) in 61 days. Of the PPL screened, 128 were positive for TB, with subsequent individual confirmation, generating a TB prevalence of 2.8% (95% CI 2.2-3.1). The highest TB prevalence was reported in the largest prison included in the study, with 2,134 participants screened in 24 days and a TB prevalence of 4.0%. The lowest prevalence was found in the smallest prison, with 472 participants screened in 8 days and a prevalence of 1.1%. 5.Conclusion: By implementing the sputum sample pooling method in mass screening, we used 60% fewer GeneXpert MTB/RIF Ultra cartridges compared to testing all participants individually, reducing costs. In settings with a high prevalence of TB, such as prisons, pooling sputum samples and mass screening can be an efficient strategy for diagnosing TB cases early, allowing screening to be performed more quickly and with fewer resources than individual testing.